Peace treaties as sources of international law - Rybicki, Rafał (Право и государство, 2020)
This article discusses the position of peace treaties within the system of international law. The article includes analysis of terms “peace treaty” and “peace agreement” in the context of international agreements treated as one of the major sources of international law (currently an international agreement is the most commonly used instrument for creating norms of international law). The authors believe that the topic itself, as well as the approach proposed by them deserve broader discussion. A peace agreement (peace treaty) is an international agreement concluded by the fighting parties, which aims for the final and lasting conclusion of the armed conflict, the establishment of peace and the restoration of normal relations between the parties. Peace treaties might be concluded by states, as well as by other entities of international law. The question of the modern peace treaties and their role in the system of international law should be treated with great attention as there are several armed conflicts ongoing around the world. In many cases, peace talks are conducted in parallel to the actual fights, with strong support of international community. Knowledge about the position of peace treaties as sources of international law is important in the process of implementation and execution of contemporary and possible future peace treaties. The article discusses several types of most common contemporary peace agreements, including both those quali-fied as 'proper' international agreements as well as other agreements that could not be treated as sources of international law (e.g. intra-state agreements between political parties). The authors conclude that that the factor that makes it possible to qualify particular international agreement as a peace treaty is the aim of final and lasting conclusion of the armed conflict, establishment of peace and the restoration of normal relations between the parties.
Keywords: international law, public international law, international agreement, peace, peace treaty, peace agreement, peace-making, sources of law, sources of international law, law of treaties